2019
DOI: 10.5194/acp-19-1867-2019
|View full text |Cite
|
Sign up to set email alerts
|

Importance of biogenic volatile organic compounds to acyl peroxy nitrates (APN) production in the southeastern US during SOAS 2013

Abstract: Gas-phase atmospheric concentrations of peroxyacetyl nitrate (PAN), peroxypropionyl nitrate (PPN), and peroxymethacryloyl nitrate (MPAN) were measured on the ground using a gas chromatograph electron capture detector (GC-ECD) during the Southern Oxidants and Aerosols Study (SOAS) 2013 campaign (1 June to 15 July 2013) in Centreville, Alabama, in order to study biosphere-atmosphere interactions. Average levels of PAN, PPN, and MPAN were 169, 5, and 9 pptv, respectively, and the sum accounts for an average of 16… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…The contributions of PN (16.7%) and AN (20.0%) exceeded HNO3 (16.2%) during summer when total NOy concentrations were lowest. Our results fall within the range of NOy budgets reported for other rural forested sites, in which PN and AN contribute  8-40% 520 (Nouaime et al, 1998;Farmer et al, 2008;Browne et al, 2013;Toma et al, 2019) and 10-22% (Day et al, 2003;Farmer et al, 2008;Browne et al, 2013) of NOy, respectively.…”
Section: Air Concentrations Of Oxidized Nsupporting
confidence: 88%
See 1 more Smart Citation
“…The contributions of PN (16.7%) and AN (20.0%) exceeded HNO3 (16.2%) during summer when total NOy concentrations were lowest. Our results fall within the range of NOy budgets reported for other rural forested sites, in which PN and AN contribute  8-40% 520 (Nouaime et al, 1998;Farmer et al, 2008;Browne et al, 2013;Toma et al, 2019) and 10-22% (Day et al, 2003;Farmer et al, 2008;Browne et al, 2013) of NOy, respectively.…”
Section: Air Concentrations Of Oxidized Nsupporting
confidence: 88%
“…Unlike PNs, ANs can also form at night via nitrate radical-induced oxidation of VOC. Further, PNs and ANs have been shown to contribute significantly to the total NOy budget in geographically diverse rural and forested environments (e.g., Trainer et al, 1993;Nouaime et al, 1998;Farmer et al, 2008;Browne et al, 2013;Toma et al, 2019). Flux measurements at 500 Blodgett Forest, CA, showed that PN dry deposition contributed 4-19% of total N deposition at the site (Wolfe et al, 2009).…”
Section: Air Concentrations Of Oxidized Nmentioning
confidence: 99%
“…The slope of the regression plot (∼12%) falls within the range of typical urban values (10%–15%) in the U.S. (Roberts, 2007) and in East Asian countries (Tanimoto & Akimoto, 2001; Tanimoto et al., 1999; Zhang et al., 2020a). Conversely, the PAN observations during the SOAS 2013 campaign showed that biogenic hydrocarbons accounted for 66% of PAN formation during the campaign with an average PPN/PAN ratio of 4.2%, which is markedly lower than PPN/PAN ratios during OPECE (Toma et al., 2019). While the observed PPN/PAN was similar to the typical urban values in the U.S., a major difference is that the PAN and PPN precursors during OPECE largely originated from urban and O&NG emissions with a large contribution of alkenes and aromatics to OH reactivity.…”
Section: Resultsmentioning
confidence: 99%
“… Scatter plots of peroxyacyl nitrate (PAN) homologs versus PAN. Solid back line indicates PANs/PAN during the ozone photochemistry and export from China experiment (OPECE) campaign (a) Green, red, yellow, and cyan lines correspond to reported peroxypropionic nitric anhydride (PPN)/PAN from Alabama during the SOAS 2013 campaign (Toma et al., 2019), fire plumes during the FIREX‐AQ campaign, Houston during the TexAQS 2000 (Roberts et al., 2001) and BAO (Lindaas et al., 2019). (b) Yellow solid and dashed lines correspond to reported median and maximum PiBN/PAN ratio from Houston.…”
Section: Resultsmentioning
confidence: 99%
“…There must therefore be another compensating mechanism responsible for NO x increase, and this is probably the reduced concentrations of NO x sinks. One of the important urban contributors to this are PANs (peroxy acetyl nitrates), and as biogenic VOCs are a major contributor to urban PAN concentrations, it can be expected that with decreased BVOC emissions, the PAN sink is reduced, resulting in higher NO x concentrations (Fischer et al, 2014;Toma et al, 2019). Another reason can lie in reaction with the OH radical, which is reduced if ozone is reduced.…”
Section: Discussionmentioning
confidence: 99%